The Implementation of Database Project :The Study of Design Process for Contemporary Menswear (Thai Fabric) - Musikapan, Ravitep (Fine Arts Journal: Srinakharinwirot University, 2011)
The study of design process for contemporary menswear (Thai fabric) is the work resulted from studying, gathering and experiment of database under the project to study the design of Thai fabric menswear funded by 2007 fiscal year budget. The budget is from the community technical service in the part of establishment of centre for implementation and development of fashion and jewelry project of Srinakarinwiroj University. It is the development of pattern for the design of menswear made of Thai fabric to make it looks universal and contemporary and to be the prototype of Thai fabric menswear. It emphasized on local silk and hand -woven cotton fabrics. The design is of deconstruction process, new Thai pattern printing in the form of minimalism. โครงการสร้างฐานข้อมูลการศึกษากระบวนการการออกแบบ เสื้อผ้าบุรุษร่วมสมัย (ผ้าไทย) การศึกษากระบวนการออกแบบเสื้อผ้าบุรุษร่วมสมัย (ผ้าไทย) เป็นผลงานที่เกิดขึ้นจากการศึกษารวบรวมฐาน ข้อมูลและทดลองใน โครงการศึกษาการออกแบบเครื่องนุ่งห่มสุภาพบุรุษผ้าไทย ที่ได้รับงบประมาณแผ่นดิน ปีพ.ศ. 2550 จากโครงการบริการวิชาการแก่ชุมชน ในส่วนโครงการจัดตั้งศูนย์การศึกษาพัฒนาแฟชั่นและอัญมณีแห่ง มหาวิทยาลัยศรีนครินทรวิโรฒ เป็นการพัฒนาลวดลายไทยเพื่อการออกแบบเครื่องแต่งกายสุภาพบุรุษจากผ้าไทย ให้ดู สากลและร่วมสมัย เพื่อเป็นต้นแบบเสื้อผ้าสุภาพบุรุษที่ใช้ผ้าไทย โดยเน้นไปที่ผ้าไหมพื้น และฝ้ายทอมือ ใช้กระบวนการ ออกแบบรูปแบบรื้อ (Deconstruction) ลวดลายไทยพิมพ์ใหม่ ในรูปแบบเสื้อผ้าแบบ มินิมอลลิสม์ (Minimalism)